Expert knowledge elicitation to generate human factors guidance for future European rail traffic management system (ERTMS) train driving models - Naghiyev, Arzoo; Sharples, Sarah; Ryan, Brendan; Coplestone, Anthony; Carey, Mike (Sage, 2017)
The European Rail Traffic Management System (ERTMS) will have an impact on the train driving task and train driver behaviour. This paper presents part of the final study of series of studies that have been conducted as part of a three-year research project, which investigated the effects of ERTMS on train drivers’ behaviours. In recent times, a number of models of train driving have been developed in order to inform train driving technology design and understand the implications of the design of the train driving task on driver performance and behaviour. An expert knowledge elicitation study was conducted to evaluate existing train driving models and to generate human factors guidance on future ERTMS train driving models. The study consisted of a workshop which was conducted using rail Human Factors (HF) experts who have been directly involved with projects examining ERTMS. Current train driving models were evaluated and ideas generated about how these should be shaped in the future to include systems such as ERTMS. The findings of the study contributed to bridging the gap between the theoretical understanding of train drivers’ cognitive strategies and practical implementation of novel technologies by the rail industry.